Production of Sterilizing Agents from Calendula officinalis Extracts Optimized by Response Surface Methodology. (7th May 2015) - Goktas, Fatih Mehmet; Sahin, Bilgesu; Yigitarslan, Sibel
Abstract : The aim of this study was to produce hand sterilizing liquid and wet wipes with the extracts of Calendula officinalis . Since this plant has well known antimicrobial activity due to its phytochemical constituents, the increase in the extraction yield was chosen as the principle part of the production process. To achieve the maximum yield, parameters of solid-to-liquid ratio, extraction temperature, and time were studied. The optimum conditions were determined by response surface methodology as 41°C, 7 h, and 3.3 g/200 mL for temperature, time, and solid-to-liquid ratio, respectively. The yield achieved at those conditions was found to be 90 percent. The highest amounts of flavonoids were detected at optimum, whereas the highest triterpene and saponin constituents were determined at different design points. The microbial efficiencies of extracts were determined by the inhibition of the growth of selected microorganisms. Different dilution rates and interaction times were used as parameters of inhibition. Not any of the constituent but symbiotic relation in-between reached the highest inhibition of 90 percent. The pH values of the extracts were 5.1 to 5.4. As a result, the extraction of Calendula officinalis at the optimum conditions can be used effectively in the production of wet wipes and hand sterilizing liquid.